Cloud Computing Training for Vocational High School Teachers and Students in Purwakarta District - Galura Muhammad Suranegara; Endah Setyowati; Ahmad Fauzi; Reza Nurfaudzan Ashsiddiq (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Cloud computing has become a pervasive technology across various industries, with both established corporations and burgeoning start-ups transitioning from on-premises data centers to cloud services, making it one of the disruptive technologies in the ongoing digital transformation. In this era of disruptive digitalization, it is imperative for Vocational High School (SMK) students to continually improve their skills and knowledge to meet the dynamic demands of the job market, not only in the present but also in unpredictable times. However, the integration of cloud computing technology into SMK curricula has been unevenly executed. To address this gap, a community service program (PKM) was carried out with the primary objective of imparting cloud computing expertise to both vocational teachers and students in Purwakarta Regency. The methodology implemented in the PkM activities combined theoretical and practical elements within each training module. Amazon Web Service (AWS) was selected as the cloud computing service platform for its prominent market share and performance compared to similar platforms so that the benefits achieved from this training could be maximized. In the long run, it is hoped that cloud computing technology is successfully implemented in SMKs throughout the region.